Self-immolation in the extinction of Menai by Chuma Nwokolo - Nkeokelonye, Adaobi; Jujar Singh, Hardev Kaur; Abdul Rani, Mohd. Zariat; Mani, Manimangai (Universiti Kebangsaan Malaysia, 2020)
This study explores the concept of self-immolation within the African literary space. It observes how people bear witness to express causes through protests, with their words, action and the self-application of lethal harm. With growing incidences of suicides around the world, self-Immolation remains peculiar generally for its politicization and likening to a sacrifice for a cause, drawing attention to social injustice and giving voice to acts of persecution which could have been voiceless. Although self-Immolation has gained interdisciplinary attention, there is an observable dearth of scholarship in the field of literature. In African literature, writers have adopted suicide as a way of dying for their characters; the much-celebrated work of Chinua Achebe gives credence to this. Studies exploring the underlying aetiology of self-inflicted deaths in novels remain sparse. In this study, we focus on The Extinction of Menai (2018) by Chuma Nwokolo, a contemporary African writer. Using the work of Emile Durkheim on Suicide as an operative framework, we explore incidences of self-inflicted deaths as a protest mechanism. We establish the use of suicide for protests by characters that cut across gender lines. We equally note the underlying cultural melody behind all acts of suicide witnessed in this novel by Chuma Nwokolo.